STK11 loss and SMARCB1 deficiency mutation in a dedifferentiated lung cancer patient present response to neo-adjuvant treatment with pembrolizumab and platinum doublet: A case report - Chen, Jianxin; Wang, Junhui (Frontiers in Oncology, 2023)
Cancers harboring serine threonine kinase (STK11) alteration or SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily B, member 1 (SMARCB1) mutation are conventionally considered as treatment-refractory to immune checkpoint inhibitors or chemotherapy, respectively. However in the present report, we demonstrated a case of dedifferentiated non-small cell lung cancer, characterized by STK11 loss (due to promoter loss) mutation co-mutated with SMARCB1 deficiency mutation, has achieved significantly partial response to neo-adjuvant treatment with pembrolizumab and platinum doublet regimen. Our case highlighted that either STK11 loss, or SMARCB1 deficiency mutation, might not be used to select patients for PD-(L)1 blockade therapy or chemotherapy, respectively. SKT11 loss accompanied with SMARCB1 deficiency mutation may benefit from immunotherapy combined with chemotherapy.